Religious Moderation's Values in Sasak Rengganis Songs - Badrun Badrun; Mutmainnah Mutmainnah (STKIP Taman Siswa Bima, 2024)
This research aims to analyze the values of religious moderation contained in the Rengganis song from the Sasak community in Lombok. Tembang Rengganis is a part of oral literature that conveys moral and religious messages through the story of Dewi Komalasari and other characters. This research employs a qualitative approach using text analysis methods and in-depth interviews with local cultural figures. The research findings indicate that this song contains values of religious moderation such as honesty, ethics, politeness, and social responsibility, as portrayed by the character Dewi Komalasari, Dewi Rengganis and Repatmaja. In addition, the antagonism displayed by the character Cupak illustrates the consequences of negative traits such as greed and envy. In conclusion, the internalization of the values contained in this song can encourage the strengthening of a moderate religious spirit within the Sasak community, particularly in maintaining social and religious harmony. This research contributes to the understanding of the importance of religious moderation in the context of local traditions.